Hexagon AgNCs/PVP Crystallization Induced Cathode Electrochemiluminescence Enhancement for miRNA221 Biosensing. Issue 10 (30th December 2022) - Wang, Bin; Wang, Guangjie; Li, Jing; Liu, Xinling; Ni, Nan; Su, Huilan; Chen, Mei; Mao, Li
Abstract: Aggredation‐induced electrochemiluminescence (AIECL) promises an efficient strategy for synthesize highly luminescent emitter and co‐reactant for ECL analysis, however, rational control of electrogenerated emission intensity is still challenging. The low electroconductivity and amorphous molecular configuration are intrinsic bottleneck. This work reveals the impact of polyvinyl pyrrolidone backbone regulated silver nanocrystallines (AgNCs/PVP) on the cathode AIECL properties in near infrared region, by employing the Box‐Behnken designed response surface computation model to modulate crystal aggregates. Electron paramagnetic resonance spectroscopy discovered hydrogen radical (HO ) dominant reductive‐oxidative (R‐O) ECL mechanism with AgNCs acting as the co‐reaction accelerator in graphene oxide/persulfate system (GO/S2 O8 2− ). Both theoretical calculation and experimental measurement testified that the ECL of AgNCs in GO/S2 O8 2− dependent on the concentration of in situ electrochemical oxidized Ag + . The high efficiency of crystallization‐induced enhanced ECL (CIECL) originates from 1) the effective electron transfer of Ag + accelerated HO produce to notable promote radioactive transition, and 2) twisted intramolecular charge transfer from the electron‐rich donor of PVP to electron‐deficient receptor of Ag 0 to restrict nonradioactive transition. The AgNCs/PVP with CIECL effect are applied to construct an ultrasensitive platform for miR‐221 assay with a lower detection limit of 7.47 × 10 3  copies mL −1 than typical qPCR method. Abstract : A hexagon AgNCs regulated by polyvinyl pyrrolidone backbone with the feature of crystallization‐induced enhanced electrochemiluminescence (CIECL) are developed in cathode co‐reaction accelerated graphene oxide/persulfate system to construct miRNA sensor. Both Box‐Behnken designed statistics and electron paramagnetic resonance spectroscopy experiment affirm that the in situ electrochemical oxidized Ag + accelerates HO dominant free radical chain reaction to break through the bottleneck of low conductivity of AIECL material.